Distribution and assessment of heavy metals in sediments of Bilaspur, Central India: Implications on ecological risk and human health hazard - Ashish Narendra Bhandari; Sangeeta (Environmental Pollution and Management)
Heavy metals, such as manganese (Mn), copper (Cu), lead (Pb), zinc (Zn), nickel (Ni), chromium (Cr), cobalt (Co), arsenic (As), mercury (Hg), and cadmium (Cd), were evaluated for accumulation, contamination, ecological risk, and human health hazard using 288 composite samples collected from the five city development zones of Bilaspur. Metal concentrations in the samples were measured using the XRF, GF-AAS, DMA, and ICP-MS techniques. The average levels of Mn, Ni, Cr, As, and Cu were significantly higher compared to the recommended US EPA guidelines. While the heavy metals pose an acceptable non-carcinogenic risk based on the human health hazard assessment, children appear more vulnerable to the imminent risk from oral ingestion. Anthropogenic-induced admixing of elements are the main causes of contamination, in the order from As>Cr>Mn>Ni>Cu. Geo-accumulation index (Igeo), contamination factor (Cf), degree of contamination (CD), and potential ecological risk (PERI) indicate that the area is unpolluted to moderately polluted, however As, Pb, and Mn pose as a looming threat. This study strives to report the most relevant, comprehensive data on the contamination of surface sediments of Bilaspur from heavy metals, with the potential hazard to human health and biodiversity.